PEMANFAATAN TEKNOLOGI DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MTs MENUJU PENDIDIKAN ISLAM YANG INKLUSIF DAN BERMAKNA - Anam, Mohamad Khoerul; Sunhaji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The rapid development of information and communication technology has transformed various aspects of human life, including Islamic education. At the Madrasah Tsanawiyah (MTs) level, the subject of Islamic Cultural History (Sejarah Kebudayaan Islam/SKI) plays a vital role in shaping students’ character through historical Islamic values. However, SKI learning often faces challenges due to its monotonous delivery and limited relevance to modern contexts. This study aims to explore the integration of technology in SKI learning as a strategic approach to creating inclusive and meaningful Islamic education. Employing a qualitative descriptive method, the research analyzes forms, benefits, and challenges of digitalization in SKI instruction. Findings show that utilizing digital media—such as interactive videos, e-learning platforms, educational games, podcasts, and virtual simulations—significantly enhances student motivation, historical comprehension, and access to learning. Moreover, digital integration fosters inclusivity by accommodating students with diverse abilities, learning styles, and geographic conditions. Despite these advantages, challenges such as inadequate infrastructure, low digital literacy, lack of contextual content, and resistance to change still hinder optimal implementation. The study concludes that a collaborative effort between educators, policymakers, and technology developers is essential to establish a sustainable digital Islamic education ecosystem. When applied effectively, technology-supported SKI learning can cultivate historically aware, tolerant, and digitally literate Muslim students prepared to face contemporary societal challenges.